2012
DOI: 10.1155/2012/728342
|View full text |Cite
|
Sign up to set email alerts
|

Protection of SH-SY5Y Neuronal Cells from Glutamate-Induced Apoptosis by 3,6-Disinapoyl Sucrose, a Bioactive Compound Isolated from Radix Polygala

Abstract: The neuroprotective effects of 3,6′-disinapoyl sucrose (DISS) from Radix Polygala against glutamate-induced SH-SY5Y neuronal cells injury were evaluated in the present study. SH-SY5Y neuronal cells were pretreated with glutamate (8 mM) for 30 min followed by cotreatment with DISS for 12 h. Cell viability was determined by (3,4,5-dimethylthiazol-2-yl)-2,5-diphenylte-trazolium bromide (MTT) assay, and apoptosis was confirmed by cell morphology and flow cytometry assay, evaluated with propidium iodide dye. Treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
362
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 287 publications
(377 citation statements)
references
References 13 publications
14
362
1
Order By: Relevance
“…According to the accessed studies, all malignant breast tumors were warmer than healthy breast tissue, regardless of their size and location 18, 21, 26, 27. However, another study observed lower increases in temperature in smaller and deeper tumors 28.…”
Section: Discussionmentioning
confidence: 99%
“…According to the accessed studies, all malignant breast tumors were warmer than healthy breast tissue, regardless of their size and location 18, 21, 26, 27. However, another study observed lower increases in temperature in smaller and deeper tumors 28.…”
Section: Discussionmentioning
confidence: 99%
“…These cell‐substrate interactions trigger cell signaling cascades and influence stem cell fate. Stem cell fate is further controlled through substrate topography, such as surface roughness of the underlying surface and isotropic or anisotropic surface patterns, but also three‐dimensional microenvironment, biochemical signals and external forces 2, 3, 4. Traditionally, cells are cultured 2D in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…However, MRI is limited in its sensitivity and specificity for biochemical changes. Those features are exactly what PET excels at: Its sensitivity in the picomolar range (10 −11 to 10 −12 mol/L) is extraordinary compared to MR sensitivity of around 10 −3 to 10 −5 mol/L 47 . Furthermore, PET has very high biochemical specificity, such that quantification of in vivo biochemistry is possible.…”
Section: Multi-modal Imaging Of Receptor Functional Dynamics Witmentioning
confidence: 62%
“…For example, the effect of direct binding of exogenous drugs has been used to evaluate antipsychotic drugs, i.e. D2 receptor antagonists, and their therapeutic window 47 . Using relevant PET radiotracers, it has been established that clinically effective doses are often between 70–90% of D2 receptor occupancy 48 .…”
Section: Types Of Challenges That Modulate Neurotransmission Andmentioning
confidence: 99%